Love the home you have eaudiobook Simple ways to embrace your style *get organized *delight in where you are. - Michaels, Melissa (Tantor Media, 2018)
What if the house of your dreams is the home you have? Meet Melissa Michaels, creator of the popular blog The Inspired Room and the best contentment coach you'll ever meet. With humor and candor Melissa reveals how to transform your rooms (and your life) from plainly livable to fabulously lovable. Like a perfectly overstuffed chair, Melissa's encouragement beckons you to get comfortable and then get creative as you: &#9679 find beauty in the ordinary &#9679 discover your style and let it shine with simple ideas &#9679 entertain possibilities and people with more gratitude and joy &#9679 gather inspiration in the 31-day Love Your Home Challenge &#9679 leap from dreamer to doer with confidence Much more than décor! This is your invitation to fall in love with the home you have and embrace the gifts of life, people, and blessings right where you are.